Strategi Pengembangan Gugusan Pulau-Pulau di Kepulauan Spermonde dalam Perencanaan Produk Perjalanan Wisata Berbasis Maritim - Ratnah Ratnah; Ruth Rinda; Matius Tinna Sarira (UNIVERSITAS NEGERI MAKASSAR, 2022)
The Spermonde Islands are a group of islands inhabited by 121 islands that are effective for development. This study aims to formulate a strategy for the development of a group of islands in the Spermonde Archipelago in the Planning of Maritime-Based Travel Products. This study uses a mixed method (Mixed Method) which begins with quantitative methods and continues with qualitative methods involving 257 respondents who were taken incidentally. Data collection techniques used in the form of questionnaires and Focus Group Discussion (FGD), interviews, comparative studies and literature studies were used for qualitative data. The results of the study show that: 1) The potential for marine tourism in the Spermonde Islands from the results of the 3A analysis: Accessibility, Amenity and Activities in general, a group of islands in the Spermonde Archipelago has the potential to become superior marine tourism with current conditions it can be said to be a natural landscape heritage. . 2) On internal factors, the strength factor has a higher score than the weakness factor so that the potential for a group of islands in the archipelago has strengths or advantages that can be developed. 3) on external factors, there is a greater opportunity factor than a threat factor so that it has a very large opportunity to be marketed in tour packages as a reliable marine destination. 4) The strategy for the development of a group of islands in the Spermonde Archipelago is prepared based on the results of the SWOT analysis and produces 13 strategies.AbstrakKepulauan spermonde merupakan gugusan pulau-pulau yang dihuni 121 pulau yang efektif untuk dikembangkan. Penelitian ini bertujuan untuk merumuskan strategi pengembangan gugusan pulau-pulau di Kepulauan Spermonde dalam Perencanaan Produk Perjalanan Wisata Berbasis Maritim. Penelitian ini menggunakan metode campuran (Mixed Method) yang diawali dengan metode kuantitatif dan dilanjutkan dengan metode kualitatif dengan melibatkan 257 responden yang diambil secara insidental. Teknik pengumpulan data yang digunakan berupa kuesioner dan Focus Group Discussion (FGD), interview, studi banding dan studi kepustakaan digunakan untuk data kualitatif. Hasil penelitian menunjukkan bahwa: 1) Potensi wisata bahari di kepulauan Spermonde dari hasil analisis 3A: Aksesibilitas, Amenitas dan Aktivitas pada umumnya gugusan pulau-pulau di kepulauan Spermonde sangat berpotensi untuk menjadi wisata bahari yang unggul dengan kondisi saat ini dapat dikatakan sebagai natural landscape heritage. 2) Pada faktor internal, faktor kekuatan mempunyai skor yang lebih besar dari faktor kelemahan sehingga potensi gugusan pulau-pulau di kepulauan mempunyai kekuatan atau keunggulan yang dapat dikembangkan. 3) pada faktor eksternal, terdapat faktor peluang lebih besar dari faktor ancaman sehingga mempunyai peluang yang sangat besar untuk dapat dipasarkan dalam paket wisata sebagai destinasi bahari yang handal. 4) Strategi pengembangan gugusan pulau-pulau di kepulauan Spermonde disusun berdasarkan hasil dari analisis SWOT dan menghasilkan 13 strategi.